2015
DOI: 10.1080/09585192.2015.1062038
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring functions and turnover intention: the mediating role of perceived organizational support

Abstract: Despite an increasing number of studies investigating the effects of mentoring on employee work outcomes, limited attention has been placed on the relationship between mentoring functions and turnover intentions. In this study, we examined the relationship between mentoring functions and turnover intentions, and the mediating role of perceived organizational support (POS) on this relationship. Using data collected from 176 employees in three Chinese banks, we found that POS partially mediated the relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 104 publications
2
64
0
6
Order By: Relevance
“…POS will increase job satisfaction. Second, the current study also corroborates the previous result regarding the negative effect of POS and turnover intention [36][37][38][39]. Finally, our result also in line with previous finding which support the negative relation between job satisfaction and turnover intention [40][41][42][43][44][45][46][47].…”
Section: A Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…POS will increase job satisfaction. Second, the current study also corroborates the previous result regarding the negative effect of POS and turnover intention [36][37][38][39]. Finally, our result also in line with previous finding which support the negative relation between job satisfaction and turnover intention [40][41][42][43][44][45][46][47].…”
Section: A Resultssupporting
confidence: 92%
“…Most studies regarding the relationship between POS and turnover intention support the significant negative relation. Hussain & Asif in Pakistan [35], Islam et al [36], Park et al in China [37], Urbonas et al in Lithuania [38], and Islam et al in Malaysia [39] found strong negative correlation (R > -0.500). Thus the hypothesis H2 is perceived organizational support will have significant and negative effect on turnover intention.…”
Section: E the Relation Of Perceived Organizational Support Andmentioning
confidence: 99%
“…Jyoti and Sharma (2015b) Career development Mentoring culture and mentoring structure 24 Park, Newman, Zhang, Wu, and Hooke (2015) Turnover intention Perceived organisational support have proven that self-efficacy influences self-control, performance, task efforts (Bandura, 1986), effective problem resolving (Gist & Mitchell, 1992), feelings of stress and anxiety (Prussia, Anderson, & Manz, 1998), coping behaviour, individual choice behaviour, effort to overcome obstacles (Stajkovic & Luthans, 1998), organisational commitment (Vuuren, DeJong, & Seydel 2008), etc. According to the mentoring theory, a mentor can provide a protégé with functions such as guidance, role modelling, and acceptance (Day & Allen, 2004).…”
Section: Moderation Hypothesesmentioning
confidence: 99%
“…Masih menurut Wahyudi (2016) karyawan akan merasa betah dengan pekerjaan yang memiliki suasana kantor kondusif dan mendukung produktivitas mereka. Faktor lain yang dapat mempengaruhi munculnya niat karyawan untuk mengundurkan diri adalah sistem rekrutmen dan seleksi yang tidak dilakukan dengan baik (Mujkic, Sehij, Rahimic, & Jusic, 2014), ketidakjelasan peran atau pekerjaan (Jaramilo, Mulki, & Solomon, 2006), karier yang tidak berkembang (Cao, Chen, & Song, 2013), tingkat keterlibatan rendah (Sultana & Jabeen, 2018), rendahnya komitmen terhadap organisasi (Susanto & Gunawan, 2013), kurangnya dukungan organisasi (Park, Newman, Zhang, Wu, & Hooke, 2015), stres kerja (Rehman, Khan, & Afzal, 2010), dan gaya kepemimpinan (Ennis, Gong, & Okpozo, 2016).…”
Section: Pendahuluanunclassified